IMPLEMENTASI STRATEGI BAURAN RITEL TERHADAP LOYALITAS PELANGGAN PADA ZONA CAFE MONTONG - Haya Nur Safa'atin; Novianti Dwi Ni’matul Auliyah (Nusantara Hasana Journal, 2025)
This study aims to evaluate the effect of retail mix strategy on customer loyalty levels at Zona Cafe Montong. The study used qualitative methods, derived from observations, interviews, and the Google Scholar database. Overall, Zona Cafe is able to build customer loyalty through the implementation of an integrated and complementary retail mix strategy, starting from a variety of distinctive and quality products, pricing that is in accordance with consumer purchasing power, strategic location selection, to effective promotion through social media and customer recommendations. Supported by a comfortable layout and friendly and efficient service, all of these aspects create a positive experience for customers, which ultimately strengthens long-term relationships and increases loyalty to Zona Cafe.